Penerapan Komunikasi Berbasis 6LoWPAN(802.15.4) Antara Node Sensor dengan IoT Middleware - Binariyanto Aji; Eko Sakti Pramukantoro; Mahendra Data (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
IoT middleware is one of the solutions of IOT Interoperability. The development of IoT middleware still needs to be developed and expanded. 6LoWPAN is an IPv6-based technology that has many advantages, beside superior on coverage, security, and scalability, 6LoWPAN is also designed for low-power devices. The purpose of this research is to realize IoT Middleware that is able to support network layer Interoperability, we want to add 6LoWPAN implementation on IoT middleware device which previously only have WLAN device. The middleware and sensor nodes will be tested for their ability to use 6LoWPAN technology, to ensure that previously running service on IoT middleware can run on 6LoWPAN technology. The results obtained are, IoT middleware can communicate with 6LoWPAN technology. Node middleware and sensor nodes can use the CoAP and MQTT protocols that stand on 6LoWPAN technology. It should be noted that CoAP and MQTT can work on the 6LoWPAN technology to ensure that the middleware node provides TCP6 and UDP6 where both protocols make CoAP and MQTT communicate based on Ipv6.